Maternal serum vitamin D and spontaneous preterm birth - A. Kalok; N.H.A. Aziz; D.A. Malik; S.A. Shah; D.N. Nasuruddin; M.H. Omar; N.A.M. Ismail; M.N. Shafiee (Clinical and Experimental Obstetrics & Gynecology)
Poor maternal vitamin D status is associated with adverse pregnancy outcomes such as preeclampsia, gestational diabetes. And increased risk of caesarean delivery. The authors conducted a prospective observational study to determine the association between maternal serum vitamin D levels and spontaneous preterm delivery. Pregnant women between 26 and 34 weeks of gestation, with symptoms of preterm labour were recruited. The control group consisted of healthy pregnant women of similar gestation age. The maternal serum vitamin D and calcium levels were measured and all women were followed up until delivery. The patients’ demographics data and their respective perinatal outcomes were collected and analysed. A total of 161 women were recruited for the study. The prevalence of vitamin D deficiency, insufficiency, and sufficiency were 41.3%, 50.9%, and 6.8% respectively (p < 0.001). The mean maternal serum vitamin D for control, threatened preterm labour, and preterm birth group were 26.5 ± 3.8 ng/mL, 17.9 ± 8.0 ng/mL, and 13.5 ± 6.98 ng/mL respectively (p < 0.001). There were no significant differences in the means of serum vitamin D among women with or without antenatal complications, such as gestational diabetes, gestational hypertension or preeclampsia. Vitamin D level was positively correlated with gestational age at delivery (p < 0.001) and newborn weight (p < 0.001). Vitamin D deficiency is associated with increased risk of spontaneous preterm labour, although there is no strong evidence of correlation with other antenatal complications. In view of high prevalence of vitamin D deficiency and insufficiency in this population, routine supplement of vitamin D maybe beneficial in reduction of premature births.